2019
DOI: 10.1002/ejp.1442
|View full text |Cite
|
Sign up to set email alerts
|

Psychological pain responses in athletes and non‐athletes with low back pain: Avoidance and endurance matter

Abstract: Background Dysfunctional psychological pain responses, namely fear‐avoidance (FAR), including catastrophizing and helplessness, as well as endurance‐related responses (ER), including thought suppression and overactivity, have been shown to be risk factors for persistent low back pain (LBP). Literature suggests that athletes may differ from non‐athletes regarding psychological responses to pain. Objectives This study set out to compare FAR and ER between athletes and non‐athletes with LBP. It was hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 75 publications
1
17
1
2
Order By: Relevance
“…The development of endurance-related pain responses might therefore be particularly important to maintain or increase their level of performance [33,34]. Indeed, "playing through" pain [35,36] or "playing hurt" [37,38] appear to be common characteristics among athletes, and some studies demonstrated more endurance-related strategies in athletes compared to non-athletes [39,40], although others reported no such differences [41][42][43]. One disadvantage of these studies is, however, that they do not distinguish between more complex patterns of pain responses.…”
Section: Introductionmentioning
confidence: 99%
“…The development of endurance-related pain responses might therefore be particularly important to maintain or increase their level of performance [33,34]. Indeed, "playing through" pain [35,36] or "playing hurt" [37,38] appear to be common characteristics among athletes, and some studies demonstrated more endurance-related strategies in athletes compared to non-athletes [39,40], although others reported no such differences [41][42][43]. One disadvantage of these studies is, however, that they do not distinguish between more complex patterns of pain responses.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure is evoked by trainers, media, and audience who expect top performance independent from injury or pain. 12 Preliminary research indicates that endurance-related pain responses apart from FAR are also associated with higher pain and disability in athletes with LBP 13 ; however, little is known about the role of psychosocial subgroups in athletes.…”
mentioning
confidence: 99%
“…[2][3][4] Chronic NS-LBP can have a long and tedious treatment that often is not a straightforward process. Psychosocial factors have been well established to have an association with chronic LBP [5][6][7] as has the advocation for including strategies to address these factors during treatment, even in athletes. 8 The lack of structural deformity or tissue damage associated with chronic NS-LBP can leave both the patients and the clinicians frustrated with the slow rehabilitation process.…”
Section: Clinical Scenariomentioning
confidence: 99%